Indeks Kinerja Jaringan Irigasi Utama Daerah Irigasi Ranah Singkuang Kabupaten Kampar - Putra, Yudhi Pramana; Rinaldi, Rinaldi; Fauzi, Manyuk (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Evaluation of irrigation system must be conducted annualy in order to know the value of performance of irrigation system of each area. The goverment want to record and maintain the existing facilities and infrastructure. However, since the transfer of authority of the Ranah Singkuang’s irrigation area in 2015 from district goverment to the to provincial goverment, there are no any operation and maintenance of Ranah Singkuang’s irrigation area. In this research, the evaluation of irrigation system performance according to Permen PU No.12/PRT/M/2015 which has been interpreted into Index of Performance of Irrigation System (IKSI). There are six parameters of this research that showed of physical infrastructure in 27,87%, plantation productivity in 12,87%, supporting facility in 8,40%, personnel organization in 10,80%, documentation in 5% and P3A in 3,60%. According this performance, total index of performance of irrigation system of Ranah Singkuang’s irrigation area is 65,14% or condition of performance is bad and need a concern.Keywords: evaluation of irrigation system, Permen PU No.12/PRT/M/2015, IKSI